2017
DOI: 10.1021/acs.jpcc.7b00286
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Hydrogen Adsorption on Au@Pd Icosahedral Nanoparticle

Abstract: First-principles calculations based on the density functional theory (DFT) were applied to study the H2 adsorption on Au@Pd NP (core@shell icosahedral bimetallic nanoparticle). The calculations indicate that, for almost all adsorption sites, there is no energy barrier for H2 dissociation at the surface of Au@Pd NP, and the H2 molecule spontaneously dissociates. The only exceptions are the case of atop from edge (AE) and atop from vertex (AV) sites, where there is no dissociation at all. Looking at the adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…On the other hand, chemically-and physically-synthesized AuPd NPs are attracting a great deal of interest due to the synergic effect of the two combined metals, Au being an excellent plasmonic material, and Pd an excellent catalytic material [22][23][24]29]. In addition to catalytic applications, these systems can exploit their functional properties in sensor applications [30][31][32], plasmonics [30,33], photocatalysis [34], hydrogen storage [35], etc. In general, the properties of NPs bridge those of bulk and atomic systems (size effects), and such properties are wide-range modifiable by the manipulation of the structural ones.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, chemically-and physically-synthesized AuPd NPs are attracting a great deal of interest due to the synergic effect of the two combined metals, Au being an excellent plasmonic material, and Pd an excellent catalytic material [22][23][24]29]. In addition to catalytic applications, these systems can exploit their functional properties in sensor applications [30][31][32], plasmonics [30,33], photocatalysis [34], hydrogen storage [35], etc. In general, the properties of NPs bridge those of bulk and atomic systems (size effects), and such properties are wide-range modifiable by the manipulation of the structural ones.…”
Section: Introductionmentioning
confidence: 99%
“…After the immobilization of the metals, no new reduction peaks were detected, confirming that the reduction of Au and Pd species was efficient upon the NaBH 4 usage; however, the shifting of the reduction temperatures to lower values (814 and 1009 °C) after the metal impregnation can be attributed to some sort of interaction between the metals and the support. The observation can be explained by H 2 absorption on the Pd or Au−Pd surfaces, which weaken the H−H bond, decreasing the H 2 activation barrier. Thus, it is more readily available for the strontium compound reduction.…”
Section: Resultsmentioning
confidence: 99%
“…The promising role of clusters in further advances for hydrogen storage materials is discussed by Jasen and coworkers, throughout the theoretical study of icosahedral Au@Pd bimetallic nanoparticles with diameter below 2 nm, involving a related 55‐atom regular icosahedra, with 42 atoms lying on the surface of an inner 13‐atom core (similar to M 13 in Figure ) . It was shown that the studied nanoclusters dissociate from the H[sbond]H bond more easily in comparison to Pd/Au surface, where the metal–metal bond remains almost unaffected indicating that the overall cluster is involved in the adsorption of H. Charge transfer shows that Au@Pd nanoparticle has a capacitive behavior, indicating that nanoparticles could adsorb more dissociated H atoms than the periodic surface, with a lesser modification of its metal–metal interaction supporting the overall cluster.…”
Section: Bare Superatomsmentioning
confidence: 94%